2022
DOI: 10.3389/fchem.2022.860398
|View full text |Cite
|
Sign up to set email alerts
|

Central-to-Folding Chirality Control: Asymmetric Synthesis of Multilayer 3D Targets With Electron-Deficient Bridges

Abstract: New multilayer 3D chiral molecules have been designed and synthesized asymmetrically through the strategy of center-to-multilayer folding chirality control and double Suzuki couplings. Individual diastereoisomers were readily obtained and separated via flash column chromatography. The key diastereoisomer was further converted into corresponding enantiomers. These enantiomers possess electron-deficient aromatic bridges layered with top and bottom aromatic scaffolds. X-ray structural analysis has unambiguously c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Since there is only a single interaction (the heavy black line in the model, Figure 8B) existing in each of the three atropisomers, there are three energy barriers instead of six in the previous atropisomerism to be expected. It should be pointed out that the nomenclature of previous molecular architectures follows the Cahn−Ingold−Prelog (CIP) rules (Tang et al, 2022b;Jin et al, 2022). However, finding a nomenclature rule for the present chirality framework seems difficult.…”
Section: Orientational Chirality Modelmentioning
confidence: 97%
See 2 more Smart Citations
“…Since there is only a single interaction (the heavy black line in the model, Figure 8B) existing in each of the three atropisomers, there are three energy barriers instead of six in the previous atropisomerism to be expected. It should be pointed out that the nomenclature of previous molecular architectures follows the Cahn−Ingold−Prelog (CIP) rules (Tang et al, 2022b;Jin et al, 2022). However, finding a nomenclature rule for the present chirality framework seems difficult.…”
Section: Orientational Chirality Modelmentioning
confidence: 97%
“…It should be pointed out that the nomenclature of previous molecular architectures follows the Cahn−Ingold−Prelog (CIP) rules ( Tang et al, 2022b ; Jin et al, 2022 ). However, finding a nomenclature rule for the present chirality framework seems difficult.…”
Section: Orientational Chirality Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past several years, our group has reported new multi-layer folding chirality of a series of molecules, including oligomers and polymers with structural flexibility, displaying physical properties on UV/Vis absorption, fluorescence, electrochemical performance, aggregation-induced emission (AIE) ( Wu et al, 2019 ; Wu et al, 2019 ; Liu et al, 2020 ; Wu et al, 2020 ; Wu et al, 2021a ; Jin et al, 2022a ; Tang et al, 2022a ; Tang et al, 2022b ; Wang et al, 2022 ), and aggregation-induced polarization (AIP) ( Tang et al, 2022c ; Tang et al, 2022d ). Among them are three-layer compounds ( Scheme 1 ), in which electron-rich ( Tang et al, 2022b ) and electron-deficient ( Jin et al, 2022a ) bridges showed distinct impacts on UV–vis absorption and fluorescence behaviors. It is worth noting that many of these compounds showed fluorescence not only in solutions but also in solid states.…”
Section: Introductionmentioning
confidence: 99%
“…The origin of AIE was made possible by restricting intramolecular motions (rotation and vibration) which limit or avoid aggregation-caused quenching (ACQ) of conventional luminophores. During our ongoing projects on multiple-layered 3D folding chirality, we found that chiral aggregates of folding monomers, oligomers, and polymers displayed strong AIE by gradually increasing water fractions (f w ) in THF-H 2 O cosolvents (Wu et al, 2019;Liu et al, 2020;Wu et al, 2020;Wu et al, 2021a;Wu et al, 2021b;Tang et al, 2022b;Jin et al, 2022;Wang et al, 2022). Interestingly, we also found these polymers showed AIE curves bounding when f w was increased to 70%, which contrast with the observation of their monomer derivatives (Wu et al, 2021b;Wang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%